К вопросу о полиномиальной сложности проблемы эквивалентности в алгебраических моделях программ - Подловченко, Р.И. (Кибернетика и системный анализ, 2012)
Розглянуто алгебраїчні моделі програм, для яких встановлено розв’язність проблеми еквівалентності. Запропоновано новий алгоритм, що допускає еквівалентність в цих моделях і походить з відомого алгоритму Мура для кінцевих автоматів. Описано клас моделей, для яких запропонований алгоритм модифікується в алгоритм поліноміальної складності. Algebraic models of programs for which the decidability of equivalence checking problem was proved are considered. A new equivalence checking algorithm stemmed from the well-known Moore’s technique for finite state automata is introduced. It is shown that for some subclasses of models this algorithm reduces to a polynomial-time equivalence checking procedure.